Practices of Local Curriculum at School Level in Jhapa District: A Review - Sunuwar, Yonden (Kanakai Journal, 2023)
Out of the subjects to be taught at the basic level (Grades 1–8) in school-level education in Nepal, one is a local subject. The main objective of this study is to analyze the local curricula developed and implemented by three municipalities (Kanakai, Birtamod, and Damak) of Jhapa district. Based on Taba's model of curriculum development and Local Curriculum Development and Implementation Guidelines, 2019, the local curricula of the three municipalities have been reviewed. As per the results obtained, the curricula of the three municipalities have clearly followed the steps of the above model and the framework of the guidelines. It was found that after ascertaining the level-wise competencies based on local needs diagnosis, the present curricula have attempted to match these competencies with the determination of course contents, content elaboration, and evaluation process. The curricula cover topics such as urban-specific social behavior, cultural-religious activities, geographical diversity, occupation and business, local environmental problems, health and yoga, special personality introduction, disaster management, etc.